Synthesis of naphthalimide-type chemsensor and its application in quality evaluation for polygonatum sibiricum Red - Wang, Zhen; Sun, Qiaoxu; Zhao, Yuanyuan; Du, Jiao; Wang, Bin (Frontiers in Chemistry, 2022)
The premise and key of ensuring the safety and effectiveness of traditional Chinese medicine (TCM) is to construct appropriate quality evaluation system of TCM. This study aimed to establish a pre-column derivatization HPLC method for achieving the quality control of Polygonatum sibiricum by reacting synthesized 4-hydrazino-1,8-naphthalimide (HAN) with diverse monosaccharides from the hydrolytic product of P. sibiricum polysaccharides (PSPs), followed by HPLC separation. The HAN was synthesized based on a CuI-catalyzed cross-coupling reaction in water, and then employed as a novel chemosensor that reacts with reducing sugars. Good separation was achieved at a detection wavelength of 448 nm using an ZORBAX SB-C8 column under a gradient elution at a flow rate of 0.5 ml/min within 12 min. The monosaccharide compositions of PSP mainly include two hexoses [glucose (Glc), galactose (Gal)] and two hexuronic acids [glucuronic acid (GlcA) and galacturonic acid (GalA)], and the molar ratio of Glc, Gal, GlcA and GalA is 16.67:52.94:10.58:19.81. The verified HPLC method, possessing excellent precision and good accuracy, successfully achieved rapid qualitative and quantitative determination for PSP. Additionally, the HAN displayed fluorescence enhancement through “push–pull” mode, and fluorescence decreased through “pull–pull” mode after binding to monosaccharides, which is a potential for fluorescence determination of different monosaccharides.